Subcellular scaling: does size matter for cell division?. (June 2018) - Heald, Rebecca; Gibeaux, Romain
Abstract : Among different species or cell types, or during early embryonic cell divisions that occur in the absence of cell growth, the size of subcellular structures, including the nucleus, chromosomes, and mitotic spindle, scale with cell size. Maintaining correct subcellular scales is thought to be important for many cellular processes and, in particular, for mitosis. In this review, we provide an update on nuclear and chromosome scaling mechanisms and their significance in metazoans, with a focus on Caenorhabditis elegans, Xenopus and mammalian systems, for which a common role for the Ran (Ras-related nuclear protein)-dependent nuclear transport system has emerged.